The pathogenic oral–gut–liver axis: new understandings and clinical implications. (3rd July 2021) - Imai, Jin; Kitamoto, Sho; Kamada, Nobuhiko
ABSTRACT: Introduction: Oral health is closely related to extra-oral disease status, as may be represented by the manifestations of gastrointestinal and liver diseases. Areas covered: This review focuses on the roles that the oral–gut or the oral–gut–liver axis play in the pathogenesis of inflammatory bowel disease, colorectal cancer, metabolic fatty liver disease, and nonalcoholic steatohepatitis. The discussion will begin with clinical data, including data from preclinical animal models, to elucidate mechanisms. We will also discuss ways to target oral dysbiosis and oral inflammation to treat gastrointestinal and liver diseases. Expert opinion: Several studies have demonstrated that oral pathobionts can translocate to the gastrointestinal tract where they contribute to inflammation and tumorigenesis. Furthermore, oral bacteria that migrate to the gastrointestinal tract can disseminate to the liver and cause hepatic disease. Thus, oral bacteria that ectopically colonize the intestine may serve as biomarkers for gastrointestinal and liver diseases. Also, understanding the characteristics of the oral–gut and oral–gut–liver microbial and immune axes will provide new insights into the pathogenesis of these diseases.